Why the Facial bone fractures in Libya different? - Mohamed Elarbi; Imbark Benjreed (Open Journal of Trauma - Peertechz Publications, 2017)
A maxillofacial fracture is a serious clinical problem because of its functional and aesthetic significance. If these injuries are treated improperly may ultimately result in a patient's low quality of life. Diagnosis and treatment of these fractures remain a challenge for oral and maxillofacial surgeons, demanding a high level of proficiency. Objective: This study aims to analyze the epidemiology of maxillofacial fractures treated in ministry hospital, Ali Omar Askar Neuro Center in Sbea Tripoli, Libya, to identify the causative factors, and to help in planning programs to control the incident in a population. Study Design: A retrospective review of all patients with maxillofacial fracture presented to Oral & Maxillofacial Surgery Department of Ali Omar Askar Neuro Center Sbea, Tripoli between January 2010   and December 2015 was performed. Result: Total of 437 patients obtained 752 maxillofacial fractures. Male were mostly affected comprising 83%, with the majority occurring in individuals 21-30 year age range. Road traffic accident was the most common cause of maxillofacial fractures with a total of 63.84%. Mandible fracture was mostly affected  consisting 59.18% of all maxillofacial fractures. The most fractured anatomical part of the mandible is parasymphysis containing 23% of all mandible fractures. Open reduction and internal fixation was the most common treatment modality. Thirteen percent of patients had associated injuries, and four percent had complications. Conclusion: According to the World Health Organization established in May 2014, Libya is the leading country of traffic deaths per capita. This retrospective study of maxillofacial fracture is congruent to the  research that road traffic accident in the country was the most common incident. It is capturing to both  government officials to implement legislation and healthcare providers to develop programs to educate  the public and reduce such injuries.